2018
DOI: 10.1140/epjc/s10052-018-5568-8
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the isotropic oscillator driven by the conformal mode

Abstract: Geometrization of a Lagrangian conservative system typically amounts to reformulating its equations of motion as the geodesic equations in a properly chosen curved spacetime. The conventional methods include the Jacobi metric and the Eisenhart lift. In this work, a modification of the Eisenhart lift is proposed which describes the isotropic oscillator in arbitrary dimension driven by the one-dimensional conformal mode.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The scalar charged particle in the monopole background that we considered is subjected to a central potential V (r) = α 2mr 2 + mω 2 2 r 2 , which is a three-dimensional analog of the AFF model's potential, and therefore the system posseses the conformal Newton-Hooke symmetry [54,55,56,57]. For coupling constant α = ν 2 , trajectories are closed only for some particular initial conditions.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The scalar charged particle in the monopole background that we considered is subjected to a central potential V (r) = α 2mr 2 + mω 2 2 r 2 , which is a three-dimensional analog of the AFF model's potential, and therefore the system posseses the conformal Newton-Hooke symmetry [54,55,56,57]. For coupling constant α = ν 2 , trajectories are closed only for some particular initial conditions.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In this subsection we derive the conformal Newton-Hooke symmetry [54,55,56,57] for the system (2.1) and compare it with the conformal symmetry of the model with ω = 0 studied in [27].…”
Section: Conformal Newton-hooke Symmetrymentioning
confidence: 99%
“…(3.11) Integrals H g , D and K of the 'regularized' AFF system generate the Newton-Hooke symmetry [55,56,10]…”
Section: Aff Conformal Mechanics Modelmentioning
confidence: 99%
“…We show that at half-integer ν, the Jordan states associated with confluent Darboux transformations enter the construction, and the spectrum of rationally deformed AFF systems undergoes structural changes.constant g = ν(ν + 1) ≥ −1/4 1 . Its non-relativistic conformal symmetry and supersymmetric extensions [5,6,7,8,9,10] find a variety of interesting applications including the particles dynamics in black hole backgrounds [11,12,13,14,15,16], cosmology [17,18,19], non-relativistic AdS/CFT correspondence [20,21,22,23,24], QCD confinement problem [25,26], and physics of Bose-Einstein condensates [27,28].On the other hand, the time-dependent Schrödinger equation for the AFF conformal mechanics model reveals a discrete Klein four-group symmetry generated by transformation of the parameter ν → −ν − 1, and by the spatial Wick rotation x → ix accompanied by the time reflection t → −t. In the picture of the stationary Schrödinger equation the time reflection transforms into the change of the eigenvalue's sign E → −E.…”
mentioning
confidence: 99%
“…Recent studies of dynamical realizations of the non-relativistic conformal algebras [1,2] revealed an interesting extension of the 1d conformal mechanics by de Alfaro, Fubini, and Furlan [3]. It describes a particle parametrized by the coordinates x i , i = 1, 2, 3, which moves along an ellipse and undergoes periods of accelerated/decelerated motion controlled by the conformal mode ρ(t)…”
Section: Introductionmentioning
confidence: 99%